Local anharmonic effects in high-Tc superconductors. Pseudospin-electron model - Stasyuk, I.V. (Condensed Matter Physics, 1999)
Some aspects of physical phenomena in high-Tc crystals caused by anharmonicity of the crystal lattice are discussed. Appropriate theoretical models are considered. A review is given of the results obtained while investigating the pseudospin-electron model (PEM) when applied to the description of structural and dielectric instabilities, phase separations and bistability phenomena. The theoretical problems are analyzed arising in PEM when the strong short-range correlations and electron transfer are taken into account simultaneously.